Cost Accounting for Management of Health Services in a Hospital - Piersiala, Luiza (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
In Polish hospitals there are clear standards for cost accounting which can be used to report information on costs and to correctly price health care services. Medical activities of hospitals are very diverse because of the existence of different types of entities and a variety of services. The article aims to discuss the essence of the subject of cost accounting in medical entities (hospitals), in particular activity‑based costing. The article includes the conclusions of the study of the literature in the field of the subject matter and legal documents concerning the Polish health care system, especially the existing costing standards, using the research method of literature and legal acts analysis. The article, in the theoretical part, presents the essence of cost accounting systems. Additionally, elements of the new legislation are presented, with the emphasis on those that are potentially important in generating cost management information. The article provides an example of the use of resource costing in a gynaecology and obstetrics department of a hospital.